2020
DOI: 10.1002/imhj.21886
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the cycle of intergenerational abuse: A qualitative interview study of men participating in a perinatal program to reduce violence

Abstract: Domestic violence and abuse in the perinatal period leads to long-term adverse outcomes for infants, including a greater risk of becoming victims or perpetrators of violence in adulthood. Examining men's beliefs about fatherhood and violence, and their motivations for engaging in programs to reduce violence, is essential to understand how interventions can impact on behavior and break intergenerational cycles of abuse. The aim of this study was to explore the experience of becoming a father in a sample of men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…Consequently, this analysis highlighted an intergenerational transmission of violence in several of the narratives of the participants. This finding aligns with other work with fathers who commit DVA (Domoney & Trevillion, 2021).…”
Section: Intergenerational Transmission Of Abusesupporting
confidence: 91%
“…Consequently, this analysis highlighted an intergenerational transmission of violence in several of the narratives of the participants. This finding aligns with other work with fathers who commit DVA (Domoney & Trevillion, 2021).…”
Section: Intergenerational Transmission Of Abusesupporting
confidence: 91%
“…Kohn 2010 ; Simpson et al, 2008 ), but a growing body of evidence now suggests that working with both partners can be very effective (Taft et al, 2016 ), e.g. when motivations for help occur within the context of parenting (Domoney & Trevillion, 2021 ). Furthermore, our findings highlight a need for perpetrator programmes to be tailored to female as well as male partners.…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional abuse was especially prominent in those reporting dual military relationships, a group currently under-represented in the military literature. The impact of such 'toxic relationships', in which bidirectional abuse occurs, on the individual partners as well as others in the household, especially children, is not sufficiently recognised (Domoney & Trevillion, 2021;Zemp et to local lockdown rules and social distancing, travel limitations and other stressors such as financial instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that high coparenting quality may buffer parenting stress (Durtschi et al, 2017 ; Steele et al, 2016 ), and more supportive coparenting is significantly associated with fewer behavioural problems among children (Choi & Becher, 2019 ). Research has also established that high coparenting quality may improve parenting strategies, and thus, may break the cycle of intergenerational abuse or trauma (Domoney & Trevillion, 2021 ; Narayan et al, 2019 ). Therefore, it is plausible to believe that high coparenting quality may exert a protective role that buffers against the intergenerational transmission of ACEs from parents to preschoolers’ behavioural problems.…”
Section: Introductionmentioning
confidence: 99%